Evaluating publications across business disciplines : inferring interdisciplinary “exchange rates” from intradisciplinary author rankings - Korkeamäki, Timo; Sihvonen, Jukka; Vähämaa, Sami (Elsevier, 2018)
We propose a novel approach to comparing publications across business disciplines. Specifically, we aim to provide an objective method for evaluating the interdisciplinary value of publications based on intradisciplinary author rankings. Using publication data from the leading journals in accounting, economics, finance, management, and marketing, we first construct intradisciplinary author rankings and then utilize these rankings to estimate the marginal effect of an additional publication on the individual's ranking within her own discipline. Based on the implied effort required to improve an individual's intradisciplinary ranking, we infer interdisciplinary “exchange rates” to evaluate the value of top-tier publications across disciplines. Our estimates indicate that the value of a single single-authored publication in a top-ranked journal is highest in accounting and lowest in marketing. We confirm the validity of our “exchange rate” approach by constructing an interdisciplinary author ranking in which authors from different disciplines are uniformly distributed across the ranking list.
Keywords: business research; discipline comparisons; journal publications; author rankings; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|